West-facing view of the subsidiary shrine to Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of a west-facing view of the subsidiary shrine to Neelkanth Mahadev Temple. Few remains of the threshold in the interiors of the temple have survived.